Pengaruh Rasio Likuiditas, Solvabilitas, Profitabilitas Terhadap Harga Saham Perusahaan Pertambangan - Putri Mbera, Kristina; Faisol; Nurdiwaty, Diah (Teewan Journal Solutions, 2025)
This study aims to investigate the impact of liquidity ratio, solvency, and profitability on the stock prices of mining companies listed on the IDX (Indonesian Stock Exchange) from 2018 to 2022. The research employs a causal-comparative technique with a quantitative approach. The population consists of mining companies listed on the IDX during the period from 2018 to 2022, totaling 40 companies, and the sampling technique used is purposive sampling. Data analysis employs multiple linear regression analysis. The test results using the t-test indicate that liquidity (Current Ratio) has no partial effect on stock prices (p-value 0.165). Solvency (Debt to Asset Ratio) also shows no partial effect on stock prices (p-value 0.529). However, profitability (Return on Asset) exhibits a significant effect on stock prices (p-value 0.001). The F-test results demonstrate that liquidity (Current Ratio), solvency (Debt to Asset Ratio), and profitability (Return on Asset) collectively influence stock prices (p-value 0.011).